A Super-Boosted Hybrid Plasmonic Upconversion Process for Photodetection at 1550 nm Wavelength - La, Ju A.; Lee, Seongyu; Hong, A-Ra; Byun, Ji Young; Kang, JoonHyun; Han, Il Ki; Cho, Younghak; Kang, Gumin; Jang, Ho Seong; Ko, Hyungduk (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2022)
A super-boosted hybrid plasmonic upconversion (UC) architecture comprising a hierarchical plasmonic upconversion (HPU) film and a polymeric microlens array (MLA) film is proposed for efficient photodetection at a wavelength of 1550 nm. Plasmonic metasurfaces and Au core-satellite nanoassembly (CSNA) films can strongly induce a more effective plasmonic effect by providing numerous hot spots in an intense local electromagnetic field up to wavelengths exceeding 1550 nm. Hence, significant UC emission enhancement is realized via the amplified plasmonic coupling of an HPU film comprising an Au CSNA and UC nanoparticles. Furthermore, an MLA polymer film is synergistically coupled with the HPU film, thereby focusing the incident near-infrared light in the micrometer region, including the plasmonic nanostructure area. Consequently, the plasmonic effect super-boosted by microfocusing the incident light, significantly lowers the detectable power limit of a device, resulting in superior sensitivity and responsivity at weak excitation powers. Finally, a triple-cation perovskite-based photodetector coupled with the hybrid plasmonic UC film exhibits the excellent values of responsivity and detectivity of 9.80 A W-1 and 8.22 x 10(12) Jones at a weak power density of approximate to 0.03 mW cm(-2), respectively, demonstrating that the device performance is enhanced by more than 10(4) magnitudes over a reference sample.